Academic Complaint Management Simulation Using the Trello Platform as a Real-Time Collaboration Tool - risna; Mida Herlina; Jumiati; Nazwa Risanti; Nafiatus Airya (LPPM Universitas Sari Mulia, 2025)
The development of information technology is driving improvements in services in higher education, including how to handle complaints about facilities and infrastructure. However, many campuses, including UINSI Samarinda, do not yet have a clear and effective complaint system. The purpose of this study was to create and test a prototype academic complaint system based on the Trello project management platform, which uses a project-based learning approach. This system manages each report as a structured